Minat Beli Generasi Z terhadap Tumbler dan Sedotan Ramah Lingkungan - Fitri, Nisa Nurul; Wulandari, Eliana; Budiman, Muhammad Arief; Ernah, Ernah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The world is currently experiencing environmental damage, it’s caused by the problem of waste that dominated by plastic. However, Generation Z as the nation's successor and information generation is expected to reduce the use of plastic to reduce environmental damage. This research focuses on Generation Z: student of Faculty of Agriculture, Padjadjaran University with the aim of 1) knowing the level of environmental awareness, attitudes, subjective norms, perceived behavioral control, and purchase intention, 2) knowing the factors that influence purchase intention for tumbler and eco-friendly straw products, and 3) the value of willingness to pay and the factors that influence it. This research was conducted using descriptive tests, multiple linear regression tests, CVM tests, and logistic regression tests. Based on the results of the analysis, it is known that the level of environmental awareness, attitudes, subjective norms, perceived behavioral control, and purchase intention are at a good level. Factors that have a significant effect are environmental awareness, attitudes, and perceived behavioral control, while subjective norms do not have a significant effect. Willingness to Pay value on tumbler is Rp.44.645 and eco-friendly straws is Rp.13.685. Willingness to Pay is influenced by gender and income.